TAXI TRANSPORT, INTERNET PLATFORMS AND MARKET LIBERALIZATION - Perišić, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Thinking about the legal regulation of the taxi services market in countries and cities around the world never stops. The emergence and use of internet platforms in the organization of passenger transport in large cities has led to the fact that anyone can find themselves in the role of a person who performs transport. Thus, taxi transport gained direct competitors, because it is clear that these two transport markets are largely substitutes. However, the existing, strict regulation of the taxi market does not recognize internet platforms and as such, prevents their functioning. The introduction of internet platforms in the transport system and their functioning in full capacity, as their creators imagined, means the previous abolition of numerous market restrictions on the taxi market, ie. liberalization.     On the other hand, the existing market restrictions on the taxi market conflict with the liberal economic concept, present primarily in the European Union, but also in the Balkan countries. This is another reason why deregulation of this market can be expected. The paper presents the characteristics of this market and identifies the most important issues of the current legislation of Serbia and Bosnia and Herzegovina that could be disputable in the process of possible deregulation. The direction in which changes in national legislation will go can be seen to some extent by analyzing the current legal framework of the European Union and the case law of the Court of Justice.